2022
DOI: 10.3389/fnins.2022.827447
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic Risk Score Effectively Predicts Depression Onset in Alzheimer’s Disease Based on Major Depressive Disorder Risk Variants

Abstract: IntroductionDepression is a common, though heterogenous, comorbidity in late-onset Alzheimer’s Disease (LOAD) patients. In addition, individuals with depression are at greater risk to develop LOAD. In previous work, we demonstrated shared genetic etiology between depression and LOAD. Collectively, these previous studies suggested interactions between depression and LOAD. However, the underpinning genetic heterogeneity of depression co-occurrence with LOAD, and the various genetic etiologies predisposing depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…In this study, we found that depression polygenicity plays a role in comorbid depression in MS and did not change based on sex nor when compared with depression occurring as the primary disease. A similar increase in the hazard (approximately 30%) for hospital-based depression diagnosis was identified in a Danish study of 34,573 individuals from the general population, 27 when depression occurred as a comorbidity of Alzheimer disease, 28 and to that of approximately 7,000 moderate-to-severe cases with MDD. 23 Our study also provides evidence of a biological basis of depression for people with MS, whereas previous studies have identified conflicting associations between a family history of depression and the occurrence of depression in MS. 29,30 This study uses a direct measure of genetic variation of depression, as opposed to family history, which captures genetic and environmental influences.…”
Section: Discussionsupporting
confidence: 66%
“…In this study, we found that depression polygenicity plays a role in comorbid depression in MS and did not change based on sex nor when compared with depression occurring as the primary disease. A similar increase in the hazard (approximately 30%) for hospital-based depression diagnosis was identified in a Danish study of 34,573 individuals from the general population, 27 when depression occurred as a comorbidity of Alzheimer disease, 28 and to that of approximately 7,000 moderate-to-severe cases with MDD. 23 Our study also provides evidence of a biological basis of depression for people with MS, whereas previous studies have identified conflicting associations between a family history of depression and the occurrence of depression in MS. 29,30 This study uses a direct measure of genetic variation of depression, as opposed to family history, which captures genetic and environmental influences.…”
Section: Discussionsupporting
confidence: 66%
“…This work applied differential gene expression and DNA-methylation analyses to study the endophenotype of depression in LOAD using a subset of the Religious Orders Study and Rush Memory and Aging Project (ROSMAP) dataset. This study extends prior work for the prediction of individuals with LOAD who are at greater risk of developing depression [ 9 , 10 ]. Collectively these studies aim to characterize the heterogeneity of depression in LOAD and further expand the field of heterogenous symptoms in LOAD by providing a guideline to study other endophenotypes of LOAD.…”
Section: Introductionsupporting
confidence: 72%
“…LOAD is characterized by multiple clinical symptoms [ 35 , 36 , 37 , 38 ], with NPS, including depression, showing high prevalence [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Prior work has explored the common genetics underlying MDD and LOAD, using genetics to predict those at greater risk of developing depression [ 9 , 10 ]. However, candidate genes and regulatory mechanisms underlying comorbid depression in LOAD have been understudied, and the transcriptomics and DNA-methylomics characteristics of depression heterogeneity in LOAD remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations